How fair are unemployment benefits? The experience of East Asia. (29th April 2019) - Hwang, Gyu‐Jin
Abstract: Despite an increasing emphasis on active labour market measures, unemployment benefits still remain a focal point of employment protection. This article takes the cases of four East Asian economies – China, Japan, Republic of Korea, Taiwan (China) –, which are often characterized as having welfare states with a strong developmental and productivist orientation, to investigate whether, as is sometimes argued, unemployment benefits are restrictive and exclusionary. In doing so, it examines the logic behind the design of unemployment benefits and argues that they are in fact progressive in design and fair when they pay out. Nonetheless, low effective coverage and low benefit rates weaken their redistribution and compensation objectives.